Minimum standards for developing Community Wildfire Protection Plans - Colorado State Forest Service, author (Colorado State University. Libraries, 2022)
The following are updated minimum standards and guidelines for developing Community Wildfire Protection Plans (CWPPs), as originally directed per Colorado Senate Bill 09-001.
CWPP minimum standards
Keywords: fire prevention; fire safety; public safety; fire protection engineering; community sustainability; natural resources; wildfires; Colorado